An overview of gelatin derived from aquatic animals: Properties and modification. (October 2017) - Lin, Lin; Regenstein, Joe M.; Lv, Shun; Lu, Jianfeng; Jiang, Shaotong
Abstract: Background: Gelatin is a multifunctional ingredient used in the food, pharmaceutical, cosmetic, and photographic industries as a gelling agent, stabilizer, thickener, emulsifier, microencapsulating agent, and film-former. The most abundant sources of gelatin are pig skins, bovine hides, and cattle bones. However, the mammalian gelatins are rejected by some consumers due to either socio-cultural-religious or health-related concerns. An alternative to mammalian gelatins are the aquatic gelatins, which are extracted from the by-products of aquatic food processing, such as the skins, bones, scales and fins of fish. Scope and approach: This review focuses on the main qualities of gelatin obtained from different aquatic animals. In addition, the strategies used to improve the properties of aquatic gelatins are discussed. Key findings and conclusions: Gelatin has been extracted from various fish species, and the physical and chemical properties of fish gelatin have been further investigated. Aquatic gelatins have very similar properties to mammalian gelatins, making them a potential substitute for pork and beef gelatins in many applications. The main limitation, however, for the use of aquatic gelatins is their weaker rheological properties when compared to mammalian gelatins. However, it is possible to improve the properties of aquatic gelatins using physical, enzymatic and natural cross-linking agents. Hopefully, gelatins derived from aquatic animals will be more widely used in various applications after modification using suitable methods. Highlights: By-products from aquatic processing are rich sources of gelatins. Aquatic gelatin is a possible alternative to bovine and porcine gelatins. The major properties of gelatins extracted from aquatic animals are investigated. Poor rheological properties have limited the application of aquatic gelatins. Physical and chemical treatments can be applied to modify the aquatic gelatins.